1993
DOI: 10.1002/1097-0142(19930201)71:3<725::aid-cncr2820710312>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity on chromosome arm 17p in small cell lung carcinomas, but not in neurofibromas, in a patient with von recklinghausen neurofibromatosis

Abstract: Background. It has been suggested that the genetic abnormality responsible for von Recklinghausen neurofibromatosis (NF1) increases a patient's risk of various kinds of malignancies. The incidence of small cell lung carcinoma (SCLC) as a complication of NF1, however, is rare. To clarify the relationship between NF1 and SCLC, possible loss of heterozygosity of chromosome 17 in a patient with SCLC combined with NF1 was analyzed. Methods. Possible loss of heterozygosity for chromosome 17 was analyzed by a molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In these three SCLC cases, tumors and normal lung tissues were stored at À80jC without fixation until DNA extraction. Cancerous and noncancerous cells of the three SCLC cases (cases 6-8) were macrodissected, and genomic DNAs were prepared as described previously (23,24). This study was undertaken according to the guidelines for medical research in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…In these three SCLC cases, tumors and normal lung tissues were stored at À80jC without fixation until DNA extraction. Cancerous and noncancerous cells of the three SCLC cases (cases 6-8) were macrodissected, and genomic DNAs were prepared as described previously (23,24). This study was undertaken according to the guidelines for medical research in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, lung malignancies reported in association with neurofibromatosis have been reported infrequently (3)(4)(5)(6)(7). Carcinosarcoma of the lung is a rare tumor, constitutes approximately 0.2-0.27% of all lung cancers, and has a poor clinical outcome (8).…”
Section: öZmentioning
confidence: 99%
“…Several cases of lung cancer in patients with NF1 have been reported in Japan and other countries (see above). As quoted below in more detail, Shimizu et al 15 failed to detect a deletion in the NF1 gene in a rare case of small cell lung carcinoma occurring in an NF1 (Table 2). Cases 1, 6, and 7 had abnormal bands (see Results for more details) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a number of malignant myeloid disorders have been reported; 19,23,24 however, several attempts have failed to detect mutations in the GRD of NF1 gene in myeloid malignancies without NF1 phenotypes. 22,25 Shimizu et al 15 reported a rare case of small cell lung carcinoma developing in a subject with NF1. Using several chromosome 17-specific polymorphic DNA markers, they looked for NF1 deletions in both primary tumor and metastatic tumors, without success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation